Pengembangan Sistem Aplikasi Manajemen Transaksi Pembelian, Penjualan dan Produksi (Studi Kasus: PT. Abadi Ario Sekawan) - Amira Ibtisama; Bayu Priyambadha; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT. Abadi Ario Sekawan is a construction company specializing in roofing construction and supplier. PT Abadi Ario Sekawan is still using simple data management and transactions with Microsoft Excel. Because in the business management is still using manual system, it causes difficulties in the provision of inventory goods. Other problems, the company does not have a system to manage the inventory goods, so to carry out all the purchase transactions, sales and production, the company is using method by estimating the remaining raw materials or goods available in the warehouse. When running the roof production, the company estimates the completion time, the amount of raw materials production by calculating the manual which impacts take longer. With these problems, this research is done to develop a transaction management system of purchase, sales and web-based production that can manage the inventory goods and the data recording of transactions. The Rough Cut Capacity Planning method is used to calculate the approximate capacity of the machine. The stages involved in the development of this system are the needs of analysis, design system, implementation and testing. Analysis of needs is done by a direct interview to the company, while the design of the system used object oriented approach. Implementation is based on design system and implemented using PHP programming language, with Codeigniter framework. Tests conducted were testing white-box, black-box and compatibility testing. The White-box testing was conducted with unit testing, the Blackbox testing was conducted with validation testing. The result of the application system testing of purchase transactions, sales and production is valid 100%.